INVESTIGATION OF AROMATICITY OF TRI AND TETRAAZANAPHTHALENE DERIVATIVES - Gümüş, Selçuk; Gümüş, Ayşegül; Avcı, Mehmet (MATTER: International Journal of Science and Technology, 2017)
Aromaticity of a compound gives important information about the possible reactions and other propeties of a molecule. In that point of view measurement of aromaticity is very important. Although there are a few applications for the determination of aromaticity, Nucleus Independent Chemical Shift calculations provide the easiest computation and best approach to the result. Naphthalene is an aromatic molecule with two fused benzene rings. It is clear that centric replacement of carbons with heteroatoms will affect the aromaticity of naphthalene. Substitution of parent carbon atoms of the ring with electronegative nitrogen atoms will decrease the aromaticity of the system. The positions of the nitrogens should also effect the aromaticity of the total system. Therefore, this work was formed by taking all the derivatives of tri and tetraazanaphthalene derivatives into consideration. In order to gain the lost aromaticity due to nitrogen substitution, ring hydrogens were substituted with electron withdrawing nitro groups